Increased plasma levels of soluble TNF receptors 1 and 2 in bipolar depression and impact of lithium treatment - Teixeira, Antonio L. (Hum Psychopharmacol, 2015)
OBJECTIVE: TNF system (TNF and its soluble receptors sTNFR1 and 2) has been investigated as a potential molecular target in bipolar disorder. The aim of the study was to compare plasma levels of these receptors in unmedicated bipolar depressed patients compared with healthy controls, and to evaluate the effects of a 6-week lithium treatment on sTNFR1 and sTNFR2 levels. METHODS: The study enrolled 29 patients with unmedicated bipolar disorder in a major depressive episode and 27 matched controls. Patients had blood collected at baseline and after 6 weeks of lithium treatment. The concentration of sTNFRs was measured by ELISA. RESULTS: sTNFR1 and sTNFR2 levels were significantly increased in bipolar depression in comparison with healthy subjects. Lithium treatment did not significantly change sTNFR1 and sTNFR2 levels from baseline to endpoint. There was no correlation between improvement in depressive symptoms and the change in sTNFR1 or sTNFR1 levels. CONCLUSION: These results reinforce the involvement of an activated immune response system in the pathophysiology of bipolar disorder, with no impact of lithium treatment on the related biomarkers.